PENGOLAHAN BAKSO DAN NUGGET DI UMKM SIPATUO SEBAGAI UPAYA PENGENTASAN STUNTING DI POLEWALI MANDAR - Ambarwati, L.; Irfan, M.; Marsudi, M. (Buletin Udayana Mengabdi; Vol 21 No 2 (2022): Buletin Udayana MengabdiDO - 10.24843/BUM.2022.v21.i02.p05, 2022)
West Sulawesi has the second highest stunting rate after East Nusa Tenggara, various efforts continue to be carried out by local governments and universities in West Sulawesi such as UNSULBAR. This service activity aims to increase the consumption of animal protein by processing livestock products, especially broiler chickens with the diversification of processed foods that are favored by children and adults such as processed meatballs and nuggets. The ingredients used to make the meatballs are broiler chicken with tapioca flour, eggs, pepper, while the nuget is made from broiler chicken with chicken eggs, bread flour, wheat flour, garlic, powdered broth, salt, sugar, and pepper. The manufacture of meatballs and nuggets begins with the provision of raw materials, refining chicken meat, adding spices and boiling the meatballs, while the nuget begins with refining chicken meat, mixing spices and meat, steaming nuggets, smearing nuget in bread flour and then frying the nuggets. Based on the results of these activities, it can be concluded that through food diversification, turning chicken meat into a delicious and nutritious food item has succeeded in increasing participants' knowledge by 30%.   Keywords: chicken meat, frozen food, meatballs, nuggets, stunting